Early Results from GLASS-JWST. XIX. A High Density of Bright Galaxies at z ≈ 10 in the A2744 Region - Marco Castellano; Adriano Fontana; Tommaso Treu; Emiliano Merlin; Paola Santini; Pietro Bergamini; Claudio Grillo; Piero Rosati; Ana Acebron; Nicha Leethochawalit; Diego Paris; Andrea Bonchi; et al. (The Astrophysical Journal Letters, 2023)
We report the detection of a high density of redshift z ≈ 10 galaxies behind the foreground cluster A2744, selected from imaging data obtained recently with NIRCam on board JWST by three programs—GLASS-JWST, UNCOVER, and DDT#2756. To ensure robust estimates of the lensing magnification μ , we use an improved version of our model that exploits the first epoch of NIRCam images and newly obtained MUSE spectra and avoids regions with μ > 5 where the uncertainty may be higher. We detect seven bright z ≈ 10 galaxies with demagnified rest frame −22 ≲ M _UV ≲ −19 mag, over an area of ∼37 arcmin ^2 . Taking into account photometric incompleteness and the effects of lensing on luminosity and cosmological volume, we find that the density of z ≈ 10 galaxies in the field is about 10× (3×) larger than the average at M _UV ≈ −21 ( −20) mag reported so far. The density is even higher when considering only the GLASS-JWST data, which are the deepest and the least affected by magnification and incompleteness. The GLASS-JWST field contains five out of seven galaxies, distributed along an apparent filamentary structure of 2 Mpc in projected length, and includes a close pair of candidates with M _UV < −20 mag having a projected separation of only 16 kpc. These findings suggest the presence of a z ≈ 10 overdensity in the field. In addition to providing excellent targets for efficient spectroscopic follow-up observations, our study confirms the high density of bright galaxies observed in early JWST observations but calls for multiple surveys along independent lines of sight to achieve an unbiased estimate of their average density and a first estimate of their clustering.